Development of scale for measuring the construct of organizational citizenship behavior from the Islamic perspective - Mohd. Israil, Khaliq Ahmad; Mohammed Kamil, Naail (Malaysian Institute of Management, 2014)
Research on organizational citizenship behaviour (OCB) has received enormous attention from researchers in the West. Quite a number of scales have been developed to measure OCB from Western perspectives emanating from Western value systems. There is a dearth of research that has attempted to develop scales for measuring OCB from other cross-cultural and religious perspectives, especially from the Islamic perspective. The present study attempts to study and propose a scale for measuring the construct of organizational citizenship behaviour from the Islamic perspective (OCBIP). Survey data employed in this empirical study was drawn from 160 Muslim employees working in majority Muslim-owned companies in the West Nusa Tenggara province of the Republic of Indonesia. After validation by subject matter experts in the fields of organizational behaviour and Islamic studies, only 31 out of the 45 total items developed to measure OCBIP were found to be valid and reliable. Assessing their psychometric properties, it was revealed that the 31 items loaded on four factors of the OCBIP scale with good psychometric indices, thus confirming the scale for measuring OCBIP in a business/ organizational context.